Quantitative assessment of erector spinae muscles in patients with Mycobacterium avium complex lung disease. (December 2018) - Asakura, Takanori; Yamada, Yoshitake; Suzuki, Shoji; Namkoong, Ho; Okamori, Satoshi; Kusumoto, Tatsuya; Niijima, Yuki; Ozaki, Akihiko; Hashimoto, Masahiro; Yagi, Kazuma; Kamata, Hirofumi; Funatsu, Yohei; et al.
Abstract: Background and objective: No reports exist regarding skeletal muscle involvement in patients with Mycobacterium avium complex lung disease (MAC-LD). The cross-sectional area of the erector spinae muscles (ESMCSA ) reflects physical activity and can be assessed by computed tomography (CT). We investigated the relationship between ESMCSA and physiological parameters and prognosis in MAC-LD patients. Material and methods: In this prospective observational study, the ESMCSA was measured on single-slice axial CT images. MAC-LD patients and sex- and age-matched controls (non-MAC-LD participants) were evaluated. We evaluated the relationship between the ESMCSA and physiological parameters and prognosis. Results: A total of 260 patients (209 female; median age, 69 years; 190 with nodular/bronchiectatic disease; 74 with cavitary lesions) were enrolled. The ESMCSA was not different between MAC-LD patients and controls. In MAC-LD patients, the ESMCSA was significantly associated with age, body mass index (BMI), pulmonary function, CT severity, and health-related quality of life (HRQL). Multivariate Cox proportional hazards analyses revealed that an ESMCSA < −1 standard derivation (hazards ratio [HR], 2.76; P = 0.047) was significantly associated with all-cause mortality, along with BMI < 18.5 kg/m 2 (HR, 3.67; P = 0.02) and presence of cavitary lesions (HR, 5.84; P = 0.001). However, the ESMCSA was not significantly associated with all-cause mortality when current treatment status, % predicted functional vital capacity, and forced expiratory volume in 1 s were added to the analyses. Conclusions: Although the prognostic impact was limited, ESMCSA was significantly associated with HRQL and prognostic physiological parameters, such as BMI and pulmonary function. Highlights: We investigated the clinical involvement of erector spinae muscles (ESMs) in MAC-LD. The cross-sectional area of ESMs (ESMCSA ) is associated with pulmonary function, severity of MAC-LD lesions, and HRQL. ESMCSA was associated with all-cause mortality along with BMI and cavitary lesions.